Shear wave elastography of breast cancer: Sensitivity according to histological type in a large cohort. (April 2016) - Evans, Andrew; Sim, Yee Ting; Thomson, Kim; Jordan, Lee; Purdie, Colin; Vinnicombe, Sarah J.
Abstract: Purpose: To define the shear wave elastography (SWE) characteristics of breast cancer histological types by size in a large cohort. Methods: Consecutive patients with US visible masses underwent SWE. All those with confirmed invasive breast cancer were included in the study. Histologic type was ascertained from core biopsy and surgical resection specimens. For each type, mean and median values for Emean and Emax were ascertained. Commoner tumour types were further analysed by invasive size. The significance of differences was established using the Chi-square test. Results: 1137 tumours constituted the study group. The proportion of tumours with Emean below 50 kPa was higher in tubular cancers (23%) compared to ductal carcinomas of no specific type (DNST) (6%) (p < 0.001). Emax below 80 kPa was seen in 34% of tubular cancers compared to 16% of DNST (p < 0.002). Emean and Emax for lobular, mucinous, papillary and metaplastic cancers were not different from those of DNST. There were no significant differences in Emean or Emax between tumour types once broken down according to invasive size. Conclusions: Most breast cancer histological types have similar SWE characteristics. The exception is tubular cancer which has significantly lower stiffness than other histologic types, accounted for largely by their small size. Highlights: Tubular cancers are softer than other tumours types. Lobular cancers have shearwave features similar to those of ductal carcinomas. Differences in shearwave findings of different tumour types are related to size.